POPULATION GROWTH AND REGIONAL STABILITY IN CENTRAL ASIA - Ibroxim Ibraximov Baxtiyor o’g’li, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Population Growth and Regional Stability in Central Asia Central Asia is one the few regions in the world where the population continuous to grow  rapidly.  While  many  countries in  Western  Europe  and  North  America  are dealing with aging populations and shrinking workforces, but Central Asian states are experiencing the opposite trend. Between 1950 and 2023, the region’s population grew from  17.5  million  to  80.8  million  (UNFPA  EECA,  2025).  Uzbekistan  is  the  most populated country in the region, with 37.4 million people in 2024, and about half of its population is under the age of 30 (Krzyżanowska, 2025; UNFPA EECA, 2025). This paper asks: How does rapid population growth influence regional stability and  labor  migration  in  Uzbekistan?  The  main  argument  is  that  population  growth creates  a  short-term  opportunity  for  economic  development,  known  as  the “demographic dividend”. But it also increases labor migration, puts pressure on cities and infrastructure, and may lead to long-term economic tension if the government does not  act.  The key  challenge  for  Uzbekistan  is  to  use  this opportunity  while  it  lasts.   The most obvious impact of the growing population in Uzbekistan is the rise in labor migration. Each year, an estimated 780,000 people enter the workforce, while the domestic economy cannot generate sufficient employment for each (UNFPA EECA, 2025).  In  consequence,  many  seek  employment  abroad;  an  estimated  2-8  million Uzbek citizens are currently working outside their country, the highest amount among the countries of Central Asia (Marat, 2009). The sum of funds transferred by migrant workers in 2024 reached 4.8 billion, equals to 14% of the country's GDP (World Bank, 2025). Whereas without remittances, the poverty rate would rise from 9.6 to 16.8% (World  Bank,  2025).  Thus,  a  substantial  portion  of  Uzbek  households  receive  the means to meet basic economic needs from the Russian, South Korean or Kazakh labor markets rather than from domestic economic development efforts by the state.